2021
DOI: 10.21203/rs.3.rs-401846/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison of self-bias measures across cognitive domains

Abstract: Background: The ‘self-bias’ – i.e., the human proneness to preferentially process self-relevant stimuli – is thought to be important for both self-related and social processing. Previous research operationalized the self-bias using different paradigms, assessing the size of the self-bias within a single cognitive domain. Recent studies suggested a reduced self-bias in autism, yet findings are inconsistent. Therefore, the primary goal of the current study was to investigate whether self-biases found across cogn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Overall, our results support previous findings that different measures of self-related processing tend not to be strongly related to each other (Amodeo et al, 2021;Nijhof et al, 2020;Woźniak & Hohwy, 2020). Moreover, our results show that even using different types of stimuli (bodily stimuli or abstract stimuli) in the same task targeting the same cognitive process (top-down preparatory activity) can lead to different patterns of results depending on which aspect of the self they target.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, our results support previous findings that different measures of self-related processing tend not to be strongly related to each other (Amodeo et al, 2021;Nijhof et al, 2020;Woźniak & Hohwy, 2020). Moreover, our results show that even using different types of stimuli (bodily stimuli or abstract stimuli) in the same task targeting the same cognitive process (top-down preparatory activity) can lead to different patterns of results depending on which aspect of the self they target.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, it has been recently demonstrated that establishing arbitrary associations between neutral stimuli and the self leads to processing advantages with respect to these stimuli, reflected by increases in accuracy and decreases in reaction times (Caughey et al, 2020;Lee et al, 2021;Sui et al, 2012;Sui et al, 2009;Sui et al, 2013;Woźniak & Knoblich, 2019;Woźniak & Knoblich, 2021). Importantly, recent studies have found that diverse self-related effects (such as those listed above) do not necessarily correlate with each other, suggesting that different cognitive processes may be underpinning each of them (Amodeo et al, 2021;Nijhof et al, 2020;Woźniak & Hohwy, 2020). If self-related processing does engage multiple distinct cognitive processes, then this raises the question which, if any, of these processes may be affected in people experiencing DP -and specifically, whether they are limited to processes of body-related information or affect self-related information in general.…”
Section: Introductionmentioning
confidence: 99%